Articulating the Inarticulate from the Margins of the State: A Post-Orientalist View - Wong, Pak Nung (Philippine Political Science Journal; Vol 30 No 53 (2009), 2009)
This essay elaborates on the theory and practice of the discursive analytical approach. This approach aims to address power asymmetry in modern knowledge production, between representing and represented. By examining the theories and practices of representation in positivism, interpretivism, structuralism and postmodernism, this essay argues for a post-Orientalist theory and practice which invetigates claims of power/knowledge of state subjects. Drawing from selected fieldwork snapshots in the Cagayan Valley, a discursive analytical approach attempts to articulate the inarticulate as, in Gramsci's term, intellectuals. It aims to encourage continuous dialogue between the representing and the represented. By seeing every indivdual as an agent of social change, it aims to encourage collaborative engagement, which renders the future of the Philippine state open to change. By continuously engageing with the state subjects serendipitously, the researcher may also serve as a venue for diverse actors to address their concerns of the Philippine state.